2009
DOI: 10.1111/j.1365-2958.2009.06931.x
|View full text |Cite
|
Sign up to set email alerts
|

Null mutations in Sinorhizobium meliloti exoS and chvI demonstrate the importance of this two‐component regulatory system for symbiosis

Abstract: SummaryExopolysaccharides, either succinoglycan or galactoglucan, are essential for the establishment of the symbiosis between Sinorhizobium meliloti and Medicago sativa (alfalfa). The ExoS/ChvI two-component regulatory system is known as a regulator of succinoglycan production but the genes that are directly regulated by ChvI have not been determined. Difficulty isolating exoS and chvI null mutants has prompted the suggestion that these genes are essential for S. meliloti viability. We have successfully isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
81
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(87 citation statements)
references
References 74 publications
6
81
0
Order By: Relevance
“…RirA is a transcriptional repressor that regulates iron acquisition and metabolism genes. ExoS-ChvI and FeuPFeuQ signaling is required for S. meliloti symbiosis (32,34), and work on related pathogenic α-proteobacteria has determined that all three regulators have critical functions during host infection (35)(36)(37).…”
Section: Ncr247 and Other Cationic Peptides Activate Three Regulons Imentioning
confidence: 99%
“…RirA is a transcriptional repressor that regulates iron acquisition and metabolism genes. ExoS-ChvI and FeuPFeuQ signaling is required for S. meliloti symbiosis (32,34), and work on related pathogenic α-proteobacteria has determined that all three regulators have critical functions during host infection (35)(36)(37).…”
Section: Ncr247 and Other Cationic Peptides Activate Three Regulons Imentioning
confidence: 99%
“…Homologs of the ChvI/ChvG two-component signal transduction system which regulates several key components of the cell envelope in rhizobia, are required for growth of R. leguminosarum, S. meliloti, and Agrobacterium spp. on complex media (4,17,32). A mutation in a periplasmic protease gene, ctpA, which has been implicated in cell envelope development results in an inability of R. leguminosarum to grow on standard complex media, and the mutant forms large, spherical cells on solid TY after incubation for 24 h (22).…”
mentioning
confidence: 99%
“…The ChvG/ChvI TCS in A. tumefaciens positively regulates a number of acid-inducible genes, including aopB, katA, virB, and virE, leading to the hypothesis that the Agrobacterium ChvG/ChvI acts as a pH sensor that regulates virulence genes in response to the acidic conditions encountered during the early stages of infection (19). In S. meliloti, a number of studies have shown that ExoS and ChvI are required for successful symbiosis with alfalfa, the host legume (2,43,45). The ExoS/ChvI TCS in S. meliloti is required for production of succinoglycan and galactoglucan, the two symbiotically active exopolysaccharides (EPSs) (2,7,43,45).…”
mentioning
confidence: 99%
“…These bacteria are uniquely adapted to survive in the rhizosphere as well as intracellularly within legume plant cells (12). During symbiosis, the cell envelope of rhizobia undergoes significant changes, and several cell envelope components are critical for a successful transition from a free living cell to an intracellular bacteroid (2,4,9,12,43). While significant attention has been focused on characterizing individual cell envelope components in free-living cells and during plant infection, a major challenge moving forward is to elucidate how rhizobia integrate multiple signals from their environment to coordinate an appropriate adaptive response to their cell envelope.…”
mentioning
confidence: 99%
See 1 more Smart Citation